Contractor All Risks (CAR) In Construction Projects - Wu, Han Yang (2013)
Contractor All Risk (CAR) insurance is one type of insurance in construction industry. It is a form of risk management, to transfer the risk of the contractor to the insurance company. This insurance separates into 2 sections. They are sections: Material damage to the work or item property; another section 2: third party liabilities such as bodily injured to the third party labours and damage to the third party property. The policy of the contractor all risk (CAR) insurance is very important to the contractor. The clauses which cover for the construction projects stated in the policy such as flood, underground pipe damage, fire and etc. some of the exclusion causes include faulty design, radioactive, nuclear and etc. every occurrence, the insured has to bear the deductibles which stated in the policy. The standard form of contract that discussed in the research as PAM contract 2006 (with quantities) and PWD 203A (Rev 2007). Some of the clause in the both of standard form is same, but some clauses are different. The research method for this research is Quantitative method. Primary data were collected through questionnaires. Total 33 valid responses and build out the feedback analysis. Most of the common losses that claim from the insurance company are the underground pipe damage. A case study of the contractor insurance had to suffer for the losses after the rejection of claims and also the wording in the contractor all risk (CAR) policy are more important than the premium they paid. The research also will list out the recommendation for further research. The focus given in this research should useful to the contractors.